Effectiveness Of Allium Tuberosum And Allium Fistulotum As Cover In Improving Green Roof Water Quality - Shari, Noraini (Universiti Sains Malaysia, 2022)
One of the Sustainable Urban Drainage Systems (SUDS) is a green roof. It have advocated the concept of control at the source in stormwater management. This concept emphasises the quantity and quality of stormwater as an integrated strategy. The influence of extensive Allium Tuberosum and Allium Fistulosum vegetated roofs on water quality was studied and installations located in USM, Nibong Tebal. The objective of the study was to determine the efficacy of Allium Tuberosum and Allium Fistulotum as green roof cover and also verify green roof leachate data follow the NWQS. The runoff quality from vegetated roofs was also compared with the runoff quality from control column. The following parameters were investigated: TP, TN, pH, colour and turbidity. The results shown that Allium Fistulosum able to reduce certain contaminants from collected rainwater in terms of turbidity, colour, TP and TN with 57%, 37%, 15% and 30% respectively. While Allium Tuberosum shown better readings in turbidity (78%) and colour (59%) except TN and TP . pH values shown both vegetations are still within the NWQS range, which is Class II and other parameter are class III and above in NWQS Apart of that the extensive vegetated roofs not obviously significance for rainwater treatment., however they can be beneficial for aesthetics, city climate, and biodiversity. Future research should be conducted on additional types of vegetation and media to identify the removal effectiveness of pollutants in green roof applications.